The Effectiveness of Using Student Worksheets Based on Problem Based Learning Class XI on Elasticity and Hooke's Law Materials on Students' Problem-Solving Ability - Normilawati Normilawati; Hadma Yuliani; Nur Inayah Syar; Nadia Azizah (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2022)
The use of learning tools such as Student Worksheets (LKS) can support the success of learning, especially Problem Based Learning (PBL) based worksheets in which there are also steps to train students' solving skills. This research aims to determine the effectiveness of using PBL-based worksheets on students' problem-solving abilities. This research is quantitative research with an experimental method (pre-experimental designs (nondesign)) with one group pretest-posttest design. The data collection technique used is in the form of description questions to measure students' problem-solving abilities. The subjects of this research were students of class XI SMA Negeri 1 Palangka Raya, amounting to 35 people. The analysis used in this research is using effect size analysis. based on the results of the research conducted, it can be concluded that the effectiveness of using PBL-based worksheets on problem-solving abilities has proven to be effective through effect size analysis with an effect size of 1.44 which is included in the high category.